Regeneration OF Ionic Liquid BMIM [SCN] from Liquid-Liquid Extraction Process - FARAH NADIA BINTI MASROL, FARAH NADIA (Universiti Teknologi Petronas, 2011)
The project focuses on 1-n-butyl-3-methylimidazolium thiocyanate, bmim [SCN] which is chosen as the ionic liquid to be experimented on. The main purpose of this particular project is to find out whether the bmim [SCN] can be regenerated by a certain process and if yes, the efficiency of the regeneration. The process which is to be developed for bmim [SCN]‘s regeneration is done so to ensure that bmim [SCN] can be reused after extraction of sulfur is done. Dibenzothiophene, DBT is chosen as the sulfur to be extracted from used bmim[SCN] as it is the most hardest sulfur compound to be removed from crude oil. DBT is also chosen because of its interaction and compatibility with the said ionic liquid, bmim [SCN]. Model oil, dodecane is used to replace crude oil because of lack of ability to obtain it. The main aim, again as mentioned above is to make full use of ionic liquid; where the performance of ionic liquid in terms of extraction and regeneration is identified. Further explanation on the ionic liquid and the processes which it is involved in is done throughout the report.